Technology Acceptance Model Of Intention To Use ICT By Academics In Nigerian Higher Education - Bundot, Garba Yohanna; Md Yunos, Jailani; Mohammed, Malina (Online Journal for TVET Practitioners, 2017)
The technology acceptance model is widely accepted and has proved applicable in identifying the intentions of users to use information communication technology (ICT) and exact usage. The theory postulates that individual attitudes are actually influenced by perceived ease of use and perceived usefulness, while behavioral intention is influenced by attitude. The purpose of this study was to determine factors that influence an individual‟s intention to use ICT based on the technology acceptance model. Nigerian Academics in the department of Science are the sampling framework of this study. A principal component analysis used to validate the constructs and variance structural equation modeling in AMOS applied to analyze the data. As anticipated, results supported the theory‟s proposition as that science lecturer‟s intention to use ICT influenced by perceived usefulness, attitude and perceived ease of use, attitude also supported. Based on the findings, hypothetical and realistic contributions were presented.